Impact of the COVID-19 pandemic on the regular follow-up and outcomes of patients with chronic myeloid leukemia in chronic-phase - Yılmaz, Umut; Küçükyurt, Selin; Tunç, Sertaç; Eşkazan, Ahmet Emre (Frontiers in Oncology, 2022)
Introduction COVID-19 immediately became a major consideration in the management of chronic myeloid leukemia (CML). The influence of such considerations on viral transmission rates and leukemic control remain to be explored. We conducted this study to identify these alterations and to investigate their clinical consequences. Methods This was a cross-sectional study, performed at a single institution on CML patients who were interviewed with a survey. We compared variables concerning new attitudes in the pandemic era between the 12-month periods before and after the pandemic onset. Outcome data were attained from the hospital archives. Findings The number of patients receiving regular outpatient care for CML in chronic phase was 210, 91% had achieved at least major molecular responses. We assessed survival, progression, number of clinical visits of all, performed the survey on 89% and evaluated molecular responses on 86.6% of these patients. The frequency of clinical and molecular monitoring was significantly reduced during the pandemic deviating significantly from the guidelines. Frequency of death, progression, loss of molecular response was not significantly increased during the pandemic era despite a few cases where the delay in assessment possibly played a role in the unfavorable outcomes. There were no COVID related deaths or disabilities. Conclusion The case-based untoward events would have probably been better managed with a more efficient communication web between patients, hematologists, and the laboratory. Therefore, it seems reasonable to consider whether such communicative paths are functional before giving up on the set schedule of CML management at times of uncertainty.